Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1953
DOI: 10.1113/jphysiol.1953.sp004883
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative study of the response to acetylcholine and histamine of the blood vessels of the human hand and forearm

Abstract: Many investigators have injected acetylcholine and histamine into man both intra-arterially and intravenously. The effects of intra-arterial injection of acetylcholine on the circulation in the legs were studied by Carmichael & Fraser (1933) who observed skin colour, and by Ellis & Weiss (1932) who measured skin temperature and arterio-venous oxygen differences. We have been unable, however, to find detailed quantitative measurements of their effects on the vessels. Since such observations were required for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1953
1953
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…Intra-arterial injections of 45-75 jug histamine (ten experiments) or 5-10 mg acetylcholine (ten experiments) during the 3rd min following the insertion of the fingers into the cold, that is, when the cold vasoconstriction was well established, did not cause a premature vasodilatation (Fig. 2a, b), although smaller doses of histamine always, and of acetylcholine usually, cause a large increase in hand blood flow at 32°C (Duff, Greenfield, Shepherd & Thompson, 1953). The complete or almost complete arrest of the circulation during the first few minutes of immersion in the cold water (Greenfield & Shepherd, 1950) must, however, restrict the amount of drug reaching the finger.…”
Section: Resultsmentioning
confidence: 99%
“…Intra-arterial injections of 45-75 jug histamine (ten experiments) or 5-10 mg acetylcholine (ten experiments) during the 3rd min following the insertion of the fingers into the cold, that is, when the cold vasoconstriction was well established, did not cause a premature vasodilatation (Fig. 2a, b), although smaller doses of histamine always, and of acetylcholine usually, cause a large increase in hand blood flow at 32°C (Duff, Greenfield, Shepherd & Thompson, 1953). The complete or almost complete arrest of the circulation during the first few minutes of immersion in the cold water (Greenfield & Shepherd, 1950) must, however, restrict the amount of drug reaching the finger.…”
Section: Resultsmentioning
confidence: 99%
“…ATP in suitable doses can cause just as large an increase in forearm and hand blood flow as does acetylcholine or histamine (Fig. 6) without the uncomfortable local bursting sensation which sometimes occurs with the former, or the facial flushing and headache associated with the latter (Duff et al 1953). …”
Section: Discussionmentioning
confidence: 99%
“…The possibility of an unequal distribution of a drug solution throughout the limb following intra-arterial infusions (Duff et al 1953) must be kept in mind when comparing the local circulatory effects of the same or different drugs on different subjects. In three subjects in the present series, the distribution was so localized that there was practically no increase in hand blood flow or in the flow through the segment of forearm inside the plethysmograph.…”
Section: Discussionmentioning
confidence: 99%
“…Feldberg and Smith (1953) have shown that large doses of 5-HT cause release of histamine from the perfused skin flap of the cat, accompanied by vasoconstriction and oedema formation. Although histamine, in a wide range of doses, injected intraarterially into the forearm or hand in man, always causes dilatation of the resistance vessels and an increase in flow (Duff, Greenfield, Shepherd, and Thompson, 1953), it is conceivable that the direct constrictor action of 5-HT on the resistance vessels might counteract the dilator action of histamine on these vessels while leaving unopposed its action on the capillaries. On the other hand, Reid (1952) demonstrated that the flush of the skin caused by intradermal injection of 5-HT was not accompanied by itching or a weal, and preliminary exp:riments in this department indicate that there is no diminution of the flush following intra-arterial injection of antihistamine.…”
Section: Subjective Effectsmentioning
confidence: 99%